Multiple origins define the genetic structure of tiger shrimp Penaeus monodon in the colombian Caribbean Sea - Juan Aguirre-Pabón; Luis Chasqui; Eider Muñoz; Juan Narváez-Barandica (Heliyon, 2023)
The tiger shrimp Penaeus monodon is a native species of the Indo-Pacific Ocean that was introduced to promote its cultivation in several American countries, including Colombia. As a result of inappropriate aquaculture practices, it has established itself in the wild in almost all the Colombian Caribbean Sea. To evaluate the genetic diversity, population structure, and origin of the founder populations, samples from three sites in the Colombian Caribbean were analyzed from 10 microsatellite loci and the mitochondrial DNA Control Region. Genetic diversity similar to native populations was found to be present in three relatively discrete populations and their origin is related to natural populations from Thailand, the Philippines, Taiwan and China. We discuss how oceanographic conditions and culture systems of tiger shrimp facilitated the success of biological invasion processes in marine ecosystems of the Colombian Caribbean.